Is TPACK-Based Academic Writing Guidebook Effective to Improve Linguistic Competence of Preservice Elementary School Teachers? - Karimatus Saidah; Rian Damariswara; Endang Sri Mujiwati; Gafarudin Fauzi Maluana (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractStudents often experience problems in linguistic aspects which affect the quality of their writing. The use of academic writing guidebooks is needed to overcome these problems. To meet the needs of students as technology users, the academic writing guidebook is presented based on the Technological Pedagogical and Content Knowledge (TPACK) approach. The aim of this research is to determine the differences in learning outcomes before and after using the guidebook presented and to determine the effectiveness of this guidebook. This research uses a quasi-experimental method with the data analysis process using the  Wilcoxon and Mann-Whitney U tests. The results of this research show that there is a significant difference between the pre-test and post-test of the experimental group. However, there was no significant difference between the experimental group and the control group. Which mean academic writing guidebook is ineffective to improve languages aspect in student academic writing skill.Keywords: TPACK, academic writing, guidebook, linguistic competence.AbstrakMahasiswa seringkali mengalami permasalahan pada aspek kebahasaan yang mempengaruhi kualitas tulisannya. Penggunaan buku panduan penulisan akademik diperlukan untuk mengatasi permasalahan tersebut. Untuk memenuhi kebutuhan mahasiswa sebagai pengguna teknologi, maka buku panduan penulisan akademik disajikan berdasarkan pendekatan TPACK. Tujuan penelitian ini adalah untuk mengetahui perbedaan hasil belajar sebelum dan sesudah menggunakan buku panduan yang disajikan dan mengetahui keefektifan buku panduan tersebut. Penelitian ini merupakan penelitian kuasi eksperimen dengan proses analisis data menggunakan uji Wilcoxon dan Mann-Whitney U. Hasil penelitian menunjukkan terdapat perbedaan yang signifikan antara pre-test dan post-test kelompok eksperimen. Namun tidak terdapat perbedaan yang signifikan antara kelompok eksperimen dan kelompok kontrol. Artinya, buku panduan penulisan akademik tidak efektif untuk meningkatkan kemampuan kebahasaan pada keterampilan menulis akademik mahasiswa.Kata kunci: TPACK, penulisan akademik, buku panduan, kompetensi linguistik.